Equilateral triangle and the Holy Trinity - Lenartowicz, J. Krzysztof (Journal of Architecture and Urbanism, 2014)
The paper deals with architectural space designed and/or built on an equilateral triangular plan, and designated for a sacred function. The author discusses the exceptional features of equilateral triangle in comparison to other central layouts. The visual attractiveness of this geometrical shape is stressed. The architectural space built on this figure has a strong semantic potential in Christian culture in Europe, since a sacred object using such a shape is associated in an easy and unambiguous manner, which also points to the popularity of patrocinium of the Holy Trinity, as well as that of the Virgin and Child with St. Anne, among the analysed structures. A comprehensive catalogue is presented of sacred objects based on an equilateral triangular plan, which have been identified in the European culture area, and were created in the period between the 12th century and contemporary times. At the nexus of the Eastern and Western Church, which differentiate their teachings in terms of interpreting the Holy Trinity (the problem of Filioque), the patrocinium and the erection of temples in the form discussed here has an exceptional meaning, especially if these shrines belong to the Uniate Church, which merges Catholicism and the Orthodox church. The types of the corner detailing have been analysed.